The association between nurses’ burnout and objective care quality indicators: a cross-sectional survey in long-term care wards - Eltaybani, Sameh (BMC Nurs, 2021)
BACKGROUND: Worldwide, rather few studies have examined the association between burnout and care quality using objectively measured quality indicators, with most of the studies have relied on perceived quality outcomes. This study aimed to examine the association between staff nurses’ burnout and selected objective quality metrics in long-term care wards in Japan. METHODS: This is a secondary analysis of a cross-sectional survey. Nurse managers and staff nurses working at randomly selected hospitals with long-term care wards—the equivalent of skilled nursing homes in Western countries— completed self-administered, anonymous questionnaires. The questionnaires collected data regarding care quality indicators, staff nurses’ burnout, and other confounders (e.g., ward size, participants’ years of experience, and patients’ conditions). All statistical analyses were conducted at the ward level. A multivariate regression analysis was used to examine associations between burnout and outcome indicators. RESULTS: Data from 196 wards in 196 hospitals (196 nurse managers and 2473 staff nurses) across Japan were analyzed. Multivariate regression analysis showed that higher emotional exhaustion was associated with higher rates of pneumonia and pressure ulcers (p-value = .036 and .032, respectively), and that reduced personal accomplishment was associated with higher rates of tube feeding (p-value = .018). A larger ward size was also associated with low rates of pneumonia (regression coefficient = −.001, p-value = .019). CONCLUSIONS: Staff nurses’ burnout is a significant determinant of care quality in long-term care wards, implying that organizations that implement burnout reducing strategies may see greater benefits in patient outcomes. A large ward size was significantly associated with better care outcomes—specifically, low rates of pneumonia. Future research needs to determine feasible quality improvement measures in small-scale long-term care facilities, and to provide more comprehensive insights on ward-level variables that influence care quality in long-term care settings.